2011
DOI: 10.1002/ardp.201100047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structural Analysis of α‐Glucosidase Inhibitors on Difference Species: A Computational Study

Abstract: Structural feature analysis of chlorogenic acid derivatives made up of varying lengths of alkyl groups as α-glucosidases inhibitors were performed by QSAR techniques. The statistically significant models derived from the study were validated by leave one out, Y-randomization and test set methods. The predictive capacity of the models was assessed by its validation parameters such as crossvalidated correlation coefficients (Q(2)), predictive residual analysis and other correlation parameters. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Specifically, the addition of a hydrocarbon chain leads to an increase in α ‐glucosidase inhibitory activity ( 3 > 4 ). As reported in the literature, a fatty alkyl group in the skeleton enhanced the activity 19 . Based on the structure of solacanin B ( 1 ), it was observed that the compound with an acetoxy group attached to C‐22 exhibited decreased inhibitory activity ( 1 < 2 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Specifically, the addition of a hydrocarbon chain leads to an increase in α ‐glucosidase inhibitory activity ( 3 > 4 ). As reported in the literature, a fatty alkyl group in the skeleton enhanced the activity 19 . Based on the structure of solacanin B ( 1 ), it was observed that the compound with an acetoxy group attached to C‐22 exhibited decreased inhibitory activity ( 1 < 2 ).…”
Section: Resultsmentioning
confidence: 77%
“…As reported in the literature, a fatty alkyl group in the skeleton enhanced the activity. 19 Based on the structure of solacanin B (1), it was observed that the compound with an acetoxy group attached to C-22 exhibited decreased inhibitory activity (1 < 2).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriocin production by LAB strain Enterococcus faecium NKR‐5‐3 was inhibited when the broth contained more than 1% of NaCl (Wilaipun et al., ). Narayana Moorthy, Ramos, and Fernandes () obtained antimicrobial activity of LAB‐produced bacteriocin ( Lactobacillus L2) at room temperature with 1% salinity, while it declined from 2% to 5%. Karthikeyan and Santhosh () showed optimum antimicrobial activity for bacteriocin of L. acidophilus at 0.9% salinity.…”
Section: Discussionmentioning
confidence: 99%
“…. NarayanaMoorthy, Ramos, and Fernandes (2012) obtained antimicrobial activity of LAB-produced bacteriocin (Lactobacillus L2) at room temperature with 1% salinity, while it declined from 2% to 5% Karthikeyan and Santhosh (2009). showed optimum antimicrobial activity for bacteriocin of L. acidophilus at 0.9% salinity.The apparent molecular weight of the semi-purified antibacterial revealed a major band at a molecular weight of 17 kDa.…”
mentioning
confidence: 97%